Content Analysis of Library Web Portals of All India Institute of Medical Sciences (AIIMS): A Case Study - Ansari, Dr. Mehtab Alam; Sharib, Mohammad; Eqbal, Naseem (Journal of Advanced Research in Library and Information Science; Vol 11 No 4 (2024): Journal of Advanced Research in Library and Information Science, 2024)
The present study aims to investigate the information on the AIIMS, New Delhi library website and emphasise its significance to students, teachers, and medical professionals. With the growing need for digital resources in healthcare libraries, the main objective is to evaluate the website’s organisation, usability, and e-resource availability. Ten major areas covering different facets of the library’s website are analysed using a thorough checklist and content analysis as a methodology. The results show that although the AIIMS library website has good navigation and e-resource offerings, it is not equipped with sophisticated accessibility features or interactive capabilities. There is a need for improvement, given its lack of Web 2.0 involvement. The digital experience at the library would be improved by increasing accessibility, encouraging user participation, and broadening the range of materials available.